EFFECTIVE DATA AND INFORMATION GOVERNANCE IN LOCAL GOVERNMENT ENVIRONMENT (Study in Kupang City) - Putri Tiara Dana Fanggidae; Rizari; Udaya Madjid (Sean Institute, 2023)
Data and information governance is a control process in data management to package data into something of value according to their needs. Effective data and information governance is able to contribute to creating constructive policies for the government. Tthis research aimsto describe effective data and information governance within the local government with a study in the government of Kupang City. The theory used is the theory of effective data governance according to Robert F. Smallwood (2014) which explains that there are 4 (four) indicators for realizing effective data and information governance namely, implementing future strategies, establishing data quality accountability, managing change, and monitor existing data governance programs. The research design used is qualitative research with a descriptive approach. The data analysis technique used is a qualitative data analysis technique, namely by collecting, condensing, presenting, and drawing conclusions.The results of the study show that data and information governance within the local government of Kupang City is not maximized, seen from inadequate infrastructure, with limited apparatus resources in terms of quantity and quality.Therefore efforts are needed, namely by providing technical training for each program manager with a non-IT educational background, collaborating with various parties who can support the provision of facilities and infrastructure, as well as improving policies in paying attention to program sustainability and budget availability in data and information management .